SOCIALIZING GAME-BASED LEARNING FOR TEACHERS AT ELEMENTARY SCHOOL IN JAKARTA PROVINCE IN INDONESIA - Desy Safitri; Sujarwo Sujarwo; Arita Marini; Nurzengky Ibrahim (Bajang Institute, 2022)
Professional teachers are required to have optimal competence in all matters relating to learning, including mastery of digital-based learning methods such as game-based learning in the face of the industrial revolution 4.0, so as to support classroom learning and be effective in delivering subject matter so that it is right on target, in order to achieve goals. predetermined learning. In order to improve teacher competence in the field of professional education for the transmission of teaching materials, socialization activities are needed for teachers to get to know game-based learning in DKI Jakarta. The urgency of this game-based learning is to provide alternative learning methods that are innovative, varied, dynamic, and not monotonous, fun, and can assist teachers in facilitating interactions between teachers and students, especially in increasing enthusiasm, motivating students to take part in learning and stimulating interest. students, so that learning becomes more effective, efficient and informative.